Eating disorders in childhood and adolescence - Lask, Bryan; Bryant-Waugh, Rachel (Routledge/Taylor & Francis Group, 2013)
"In the fourth edition of this accessible and comprehensive book, Bryan Lask and Rachel Bryant-Waugh build on the research and expertise of the previous three editions. First published in 1993, this was the first book of its kind to explore eating disorders in children and young adolescents, a population that is very different from those in their late teens and adulthood. The contributors' experience and knowledge have increased and the field has moved forward over the past 20 years. This fully revised edition offers a distillation of current information relating to the younger population, and contains brand new chapters on areas of experience, research and practice including: the perspective of a young person going through an eating disorder; experiences of a parent; updated information regarding advances from neuroscience; therapeutic engagement; and cognitive remediation therapy. Eating Disorders in Childhood and Adolescence offers the reader knowledge, insight and understanding into this fascinating but challenging patient group. It has both a clinical and research focus and will be an essential text for a wide range of professionals, as well as being readable for parents of children suffering from eating disorders"--Publisher's description